A cluster randomized controlled trial comparing the effectiveness of an individual planning intervention with collaborative planning in adolescent friendship dyads to enhance physical activity (TWOgether) - Theda Radtke; Aleksandra Luszczynska; Konstantin Schenkel; Stuart Biddle; Urte Scholz (BMC, 2018)
Abstract Background Most adolescents do not meet the recommendations for physical activity (PA) of at least 1 h per day. Individual planning (IP) interventions, including forming plans for when, where and how (action planning) to engage in a behavior, as well as the planning for how to deal with arising barriers (coping planning), are effective to enhance PA in adults. Collaborative planning (CP) is conjoint planning of two individuals regarding a behavior which is performed together. It is assumed that CP stimulates social exchange processes between the planning partners. However, it remains unclear whether planning interventions of PA in adolescents are successful and which planning intervention is more effective. Thus, this cluster randomized controlled trial (RCT) examines changes in daily moderate-to-vigorous PA in adolescents' friendship dyads resulting from planning. Individual self-regulating mechanism and social exchange processes are proposed as mediating mechanisms of the effects of planning for health behavior change. Methods A single-blind four-arm parallel-group cluster-RCT is used. The sample consists of 400 friendship dyads between 14 and 18 years of age. As the recruitment takes place in schools, a cluster randomization of the schools is used to enroll dyads to (a) an IP intervention, (b) a CP intervention or (c) one of the two no-planning control conditions. Devise-measured and self-reported PA as the primary outcomes, self-regulatory strategies, and social exchange processes as secondary outcomes are assessed at three or four time points. After baseline measurement, the baseline ecological momentary assessment of the main variables takes place for 8 days followed by the intervention and a 7-days diary phase. Follow-ups are 1 month and 6 months later. Subsequent to the six-month follow-up, another 7-days diary phase takes place. Discussion This is the first study examining IP in comparison to CP in adolescents applying a single-blind cluster RCT. Consequently, the study allows for understanding the efficacy of individual and collaborative planning and the underlying mechanisms in adolescent dyads. Trial registration This RCT was funded by the Swiss National Science Foundation (100019_169781/1) and was registered on 18/06/2018 at ClinicalTrials.gov: NCT03575559.